Modelling the Development of Rocky Shoreline Profiles along the Northern Coast of Ireland - EDWARDS, ROBIN (My University, 2013)
A mathematical wave-erosion model is used to simulate postglacial shoreline profiles along the rocky, high energy coast of the north of Ireland. The wave erosion model is driven by a suite of relative sea-level (RSL) curves for the last 16000 years produced from four glacial rebound models. Multiple runs are performed with different initial shore profiles and rock resistances to investigate shoreline evolution and the significance of inherited morphology on the resultant profile shape. The simulated profiles, which encompass supratidal, intertidal and subtidal environments, are then compared with mapped profiles from three areas of the north of Ireland with different lithological and hydrographic properties. The mapped profiles are compiled from detailed analysis of high resolution (1 m) swath bathymetry and backscatter data, which is used to compile a database of seafloor morphology, submerged shore platform location, depth and characteristics. Modelled profiles generally replicate the overall mean shoreline gradients observed across the region when rock resistance is relatively high and erosion rates correspondingly low. In these profiles, breaks in mean slope are observed at depths comparable to the RSL minima in several of the RSL scenarios (at c. -10m, -15m and -20m for North Antrim, Derry and Donegal respectively). At Portrush and Portballintrae (Derry), profiles may be influenced by structural controls relating to the underlying basalt surface and the removal of overlying glaciogenic sediments. All RSL scenarios replicate the observed eastward increase in cliff-platform junction height, reflecting the differential glacioisostatic rebound experienced along the coast. However, the precise elevation at which the simulated cliff base occurs is sensitive to the choice of RSL scenario, suggesting that this parameter may prove useful in evaluating glacial rebound model performance. Several of the RSL scenarios generate raised shore platforms or terraces in North Antrim and Derry at heights comparable to raised shoreline features reported in the literature. However, no single curve or combination of parameters is capable of generating the range of platform and terrace features observed in the bathymetric and topographic data. Notably, a wide sub-horizontal platform at -7 to -8 m in the western part of Ballycastle Bay could not be simulated satisfactorily. These misfits are consistent with the idea that many rock platform or terrace features are inherited from an earlier phase or phases of RSL. The model outputs presented here provide a broad, first-order assessment of shore profile development across the region, and illustrate the insights that can be gained by combining wave and glacial rebound models. Further work is now required to add detail to this general framework, both through the refinement of models and their parameters, and by the collection of new field data concerning wave and rock characteristics, platform morphology and its relationship to other shoreline features.
PUBLISHED
Keywords: wave erosion; model; relative sea level; rock coast; shore platforms; marine terraces; Smart & Sustainable Planet